2020
DOI: 10.1002/agm2.12095
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic senescence and its clinical manifestations

Abstract: The pancreas is a vital organ which has both endocrine and exocrine functions and plays an essential role in food digestion and glucose metabolism. Pancreatic structure and function undergo a series of changes with aging and senescence. Pancreatic exocrine and endocrine function gradually change, which may lead to conditions such as dyspepsia and diabetes mellitus. Hence, clinicians need to be familiar with the characteristics of pancreatic senescence. This article reviews the manifestations of pancreatic sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The main pancreatic duct became slightly dilated. 8 It could be found that when observing human organs in the Opposed‐Phase T1 weighted sequence images, the tissue edges could be better displayed, which was convenient for description and measurement. MR technology was more sensitive in diagnosis of pancreatic cysts than computerized tomographic scan.…”
Section: Discussionmentioning
confidence: 99%
“…The main pancreatic duct became slightly dilated. 8 It could be found that when observing human organs in the Opposed‐Phase T1 weighted sequence images, the tissue edges could be better displayed, which was convenient for description and measurement. MR technology was more sensitive in diagnosis of pancreatic cysts than computerized tomographic scan.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic volume reaches its maximum (~78.85 cm 3 ) in the third decade of life, and then pancreatic volume decreases with advancing age, reaching~57.35 cm 3 at the age of 70-80 years [90,92], while its hardness is increased [93], and the pancreatic ductal structure is dilated and shows a tendency to enlargement with advancing age [90,94]. An increased fibrosis around the acini, islets, and extracellular matrix is observed along with an apparent fatty infiltration [91,95,96]. At the ultrastructural level, several changes are observed with age, including mitochondrial swelling, vacuolization, and increased lipid droplets, lysosomes, and autophagosomes [91].…”
Section: Aging and Pancreasmentioning
confidence: 99%
“…Aging is accompanied by several changes in pancreatic structure and function [90,91]. Pancreatic volume reaches its maximum (~78.85 cm 3 ) in the third decade of life, and then pancreatic volume decreases with advancing age, reaching~57.35 cm 3 at the age of 70-80 years [90,92], while its hardness is increased [93], and the pancreatic ductal structure is dilated and shows a tendency to enlargement with advancing age [90,94].…”
Section: Aging and Pancreasmentioning
confidence: 99%
See 2 more Smart Citations